MENINGKATKAN KEMAHIRAN BERBAHASA MELALUI APRESIASI SASTRA PESERTA DIDIK TINGKAT SEKOLAH DASAR DI KOTA MEDAN - Suyadi nfm; Syaifuddin Zuhri Harahap; Imran Nfm (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This paper is the result of research on language proficiency through literary appreciation of learners in the city of Medan. the research was conducted in several stages in three sub-districts, namely Medan Belawan, Medan Marelan, and East Medan. Through a random system, we tested learners with writing and reading tests. We found data that language proficiency through literary appreciation of elementary school students is strongly influential. The results of language proficiency tests through literary appreciation achieve a very positive relationship. Positive results that can already be seen from the results of the ability to compose and read the contents of the essay. The mean, median, and reading test results showed that eleven respondents scored the lowest and four respondents rated the highest. While that has a mean value or mean of 77.03 ranges in the range of values 75-79, 9 that is around 8 respondents. Despite a slight difference in the mean value position, the range of reading test scores has in common with the composing test, which is 75-79.9. However, the average results of the test made up more (18 respondents) than the reading test results (8 respondents). For the median or median between the writing test and the reading test has in common is 78.6, although the middle score winner is smaller (eight respondents) than the writing test (18 respondents) in the 75-79.9 range. While the value that often appears (mode) is 81.87 which is owned 18 people in the range of values 80-84.9. Furthermore, using the Pearson Product Moment formula           r = nΣxy - (Σx) (Σy)                √ {nΣx² - (Σx) ²} {nΣy2 - (Σy) 2}we found the correlation coefficient between language proficiency and literary appreciation of elementary school students in Medan City is 1.87, meaning that both variables has a strong relationship and the relationship form is Linear Positif.